Establishing Sustainable Arthroscopy Capacity in Low- and Middle-Income Countries (LMICs) through High-Income Country/LMIC Partnerships: A Qualitative Analysis. Issue 3 (5th July 2022) - von Kaeppler, Ericka P.; Coss, Nathan; Donnelley, Claire A.; Atkin, Dave M.; Tompkins, Marc; Haonga, Billy; Molano, Alberto M.V.; Morshed, Saam; Shearer, David W.
Abstract : Background: Disparities exist in treatment modalities, including arthroscopic surgery, for orthopaedic injuries between high-income countries (HICs) and low- and middle-income countries (LMICs). Arthroscopy training is a self-identified goal of LMIC surgeons to meet the burden of musculoskeletal injury. The aim of this study was to determine the necessary "key ingredients" for establishing arthroscopy centers in LMICs in order to build capacity and expand training in arthroscopy in lower-resource settings. Methods: This study utilized semi-structured interviews with orthopaedic surgeons from both HICs and LMICs who had prior experience establishing arthroscopy efforts in LMICs. Participants were recruited via referral sampling. Interviews were qualitatively analyzed in duplicate via a coding schema based on repeated themes from preliminary interview review. Subgroup analysis was conducted between HIC and LMIC respondents. Results: We identified perspectives shared between HIC and LMIC stakeholders and perspectives unique to 1 group. Both groups were motivated by opportunities to improve patients' lives; the LMIC respondents were also motivated by access to skills and equipment, and the HIC respondents were motivated by teaching opportunities. Key ingredients identified by both groups included an emphasis on teaching and the need for high-cost equipment, such as arthroscopy towers. The LMIC respondents reported single-use materials as a key ingredient, while the HIC respondents reported local champions as crucial. The LMIC respondents cited the scarcity of implants and shaver blades as a barrier to the continuity of arthroscopy efforts. Conclusions: Incorporation of the identified key ingredients, along with leveraging the motivations of the host and the visiting participant, will allow future international arthroscopy partnerships to better match proposed interventions with the host-identified needs. Clinical Relevance: Arthroscopy is an important tool for treatment of musculoskeletal injury. Increasing access to arthroscopy is an important goal to achieve greater equity in musculoskeletal care globally. Developing successful partnerships between HICs and LMICs to support arthroscopic surgery requires sustained relationships that address local needs.